WOMEN’S RESISTANCES AGAINST OPPRESSIONS IN THE DAMSEL MOVIE - Titania Dwi Arzety Arzety; Sulasih Nurhayati; Widya Nirmalawati; Titik Wahyuningsih (Lire Journal (Journal of Linguistics and Literature), 2026)
This research explores women’s resistance and empowerment to systemic oppression in the movie Damsel (2024) through the theoretical lenses of Iris Marion Young’s “Five Faces of Oppression” and Rosemarie Tong’s radical feminism. The movie tells a story of Elodie, a young noblewoman sacrificed by the royal monarchy to a dragon under the guise of marriage tradition. The study aims to identify the forms of oppression Elodie experiences and to analyze the strategies she employs to reclaim her agency. Using Young’s framework, the analysis reveals how Elodie endures five kinds of oppression, including exploitation, marginalization, powerlessness, cultural imperialism and violence. Elodie experiences physical aggression, loses her autonomy, is stigmatized due to her gender and class, and is politically exploited. Applying Tong’s interpretation of radical feminism, the research further explores Elodie’s development not merely as a survivor but as an empowered agent who actively resists patriarchal domination. The results show that her rejection of prescribed gender roles, her assertion of bodily and political autonomy, and her strategic confrontation with the monarchy exemplify radical feminist resistance aimed at transforming unjust structures. The study concludes that her final act of dismantling the oppressive system not only secures her own liberation but also creates possibilities for broader collective empowerment for other women within the narrative.